Fermi-arc diversity on surface terminations of the magnetic Weyl semimetal Co3Sn2S2 - Morali, Noam; Batabyal, Rajib; Nag, Pranab Kumar; Liu, Enke; Xu, Qiunan; Sun, Yan; Yan, Binghai; Felser, Claudia; Avraham, Nurit; Beidenkopf, Haim (Science, 2019)
Bulk-surface correspondence in Weyl semimetals ensures the formation of topological "Fermi arc" surface bands whose existence is guaranteed by bulk Weyl nodes. By investigating three distinct surface terminations of the ferromagnetic semimetal Co3Sn2S2, we verify spectroscopically its classification as a time-reversal symmetry-broken Weyl semimetal. We show that the distinct surface potentials imposed by three different terminations modify the Fermi-arc contour and Weyl node connectivity. On the tin (Sn) surface, we identify intra-Brillouin zone Weyl node connectivity of Fermi arcs, whereas on cobalt (Co) termination, the connectivity is across adjacent Brillouin zones. On the sulfur (S) surface, Fermi arcs overlap with nontopological bulk and surface states.We thus resolve both topologically protected and nonprotected electronic properties of a Weyl semimetal.
CRIS-Team Scopus Importer:2022-04-14